2015
DOI: 10.1038/ncomms8562
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 induces antiviral microRNA-29 in CD4 T cells to limit HIV-1 infection

Abstract: Initial events after exposure determine HIV-1 disease progression, underscoring a critical need to understand host mechanisms that interfere with initial viral replication. Although associated with chronic HIV-1 control, it is not known whether interleukin-21 (IL-21) contributes to early HIV-1 immunity. Here we take advantage of tractable primary human lymphoid organ aggregate cultures to show that IL-21 directly suppresses HIV-1 replication, and identify microRNA-29 (miR-29) as an antiviral factor induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 67 publications
2
57
1
Order By: Relevance
“…It has been observed that HIV infection causes changes in the profile of some miRNA such as miR-29a, miR-29b, miR-125b, miR-223, miR-382, miR-198, etc. This changes have been observed in infected CD4 + T cell, PBMCs or serum [1][2][3]6,[8][9][10][19][20][21]. However, it should be taken into account that miRNAs may be regulated in different ways providing different profiles depending on the different immune compartments.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…It has been observed that HIV infection causes changes in the profile of some miRNA such as miR-29a, miR-29b, miR-125b, miR-223, miR-382, miR-198, etc. This changes have been observed in infected CD4 + T cell, PBMCs or serum [1][2][3]6,[8][9][10][19][20][21]. However, it should be taken into account that miRNAs may be regulated in different ways providing different profiles depending on the different immune compartments.…”
mentioning
confidence: 95%
“…For example, miR-150 in HIV infected patients is much higher in plasma than in the cell compartments [1]. Cellular miRNA play a critical role in the pathogenesis of HIV intervening in viral infection, latency and mediating cell intrinsic resistance [6,10,19]. Here, we will focus on the role of miRNAs as innate antiretroviral defense.…”
mentioning
confidence: 99%
See 3 more Smart Citations